Upaya Pengembangan Empat Destinasi Pariwisata Unggulan Berbasis Masyarakat (Community-Based Tourism) dalam Mendorong Pertumbuhan Ekonomi Masyarakat Lokal di Kabupaten Buol - Mutiara R. Pangulu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Community-Based Tourism is a concept that emphasizes the active involvement of local communities in connecting their natural environment and cultural heritage with tourists. Therefore, the implementation of this approach is highly relevant for Buol Regency, which has four leading tourism destinations. The results of the study indicate that destination development has been carried out through the improvement of basic facilities, area arrangement, tourism promotion, and community group empowerment. Community participation is reflected in the provision of culinary services, the sale of local products, the management of tourism areas, as well as environmental cleanliness and security activities. The conclusion of this study shows that the development of the four leading tourism destinations in Buol Regency has demonstrated a positive direction in promoting local economic growth. However, the sustainability and optimization of economic benefits largely depend on the synergy between local government, managers, and the community.